Pengaruh Konsep Diri Dan Forgiveness Terhadap Psychological Well-Being Pada Mahasiswa - Afiifah oktafiani rahmadini nurul khootimah; Afrian riziq; Suniyah salasilla; Lucky purwantini (Pusat Riset dan Inovasi Nasional, 2024)
Psychological well-being indicates an individual's ability to make life decisions independently, master their environment, establish positive relationships with other people, determine and achieve life goals, accept themselves positively, and develop their potential gradually. This research aims to determine the influence of self-concept and forgiveness on psychological well-being. This research uses quantitative methods. The subjects in this research were 134 students of the psychology study program at the Islamic University